ENT530: De Sambal / Nur Nadira Nadia Majid … [et al.] - Majid, Nur Nadira Nadia; Hidzir, Umminadiera; Harun, Nadiatulnaim; Azhar, Nor Azila (2019)
Our team produce a homemade based on 'sambal’ product that is made 100% quality ingredients. We provide safe and delicious sambal that can be consume by everyone. The unique of this product is we produce this sambal with a very good quality product and that will be our signature product. For our product, the potential markets that we are targets mostly students and resident around Shah Alam. The projection that we will face is that we are a newbie and lack of knowledge in doing business. There are also a few competitors that sell the same products as us which they already have loyal customers in their business. With all of our commitment and fully cooperation with each partner, we are confident that we will succeed in doing this business. Also, we will try to promote our business to ensure this business growth bigger from day-to-day. We will focus on give the best services than other competitors and gain as much profit so that, we can expand our business and become a wellknown Muslim supplier to supply a good quality homemade product around Malaysia and soon to the whole world.